Re‐evaluation of glutamic acid (E 620), sodium glutamate (E 621), potassium glutamate (E 622), calcium glutamate (E 623), ammonium glutamate (E 624) and magnesium glutamate (E 625) as food additives. (12th July 2017) - ,; Mortensen, Alicja; Aguilar, Fernando; Crebelli, Riccardo; Di Domenico, Alessandro; Dusemund, Birgit; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Leblanc, Jean‐Charles; Lindtner, Oliver; et al.
Abstract: The EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) provides a scientific opinion re‐evaluating the safety of glutamic acid–glutamates (E 620–625) when used as food additives. Glutamate is absorbed in the intestine and it is presystemically metabolised in the gut wall. No adverse effects were observed in the available short‐term, subchronic, chronic, reproductive and developmental studies. The only effect observed was increased kidney weight and increased spleen weight; however, the increase in organ weight was not accompanied by adverse histopathological findings and, therefore, the increase in organ weight was not considered as an adverse effect. The Panel considered that glutamic acid–glutamates (E 620–625) did not raise concern with regards to genotoxicity. From a neurodevelopmental toxicity study, a no observed adverse effect level (NOAEL) of 3, 200 mg monosodium glutamate/kg body weight (bw) per day could be identified. The Panel assessed the suitability of human data to be used for the derivation of a health‐based guidance value. Although effects on humans were identified human data were not suitable due to the lack of dose–response data from which a dose without effect could be identified. Based on the NOAEL of 3, 200 mg monosodium glutamate/kg bw per day from the neurodevelopmental toxicity study and applying the default uncertainty factor of 100, the Panel derived a group acceptable daily intake (ADI) of 30 mg/kg bw per day, expressed as glutamic acid, for glutamic acid and glutamates (E 620–625). The Panel noted that the exposure to glutamic acid and glutamates (E 620–625) exceeded not only the proposed ADI, but also doses associated with adverse effects in humans for some population groups.